Desenvolvimento de Sensores Baseados em Grades de Bragg para Instrumentação em Exoesqueleto de Membro Inferior - Sanchez, Manuel Ricardo Alfonso (2020)
Conventional technologies to monitor kinetic and comfort variables in robotic exoskeletons and in human-robot interfaces are in general: bulky, sensitive to misalignments and do not allow for multiplexed operation. Optical sensors based on fiber Bragg gra